IMPLEMENTASI PENDIDIKAN KARAKTER PEDULI LINGKUNGAN DI SEKOLAH DASAR - Sofiana Haul; Yosef Firman Narut; Mikael Nardi (Jurnal Literasi Pendidikan Dasar (JLPD), 2021)
The aims of this study are: 1) to determine the implementation of environmental awareness character education in elementary schools; 2) to describe the obstacles faced in the implementation of environmental awareness character education in elementary schools; 3) to describe the tips taken to support the success of environmental awareness character education in elementary schools. This environmental awareness character needs to be formed from an early age, namely, at elementary school age. The writing method used is a literature study which contains theories relevant to the research problem. The data sources in this study were secondary sources that relevant to the research variables. Data collection techniques was carried out by tracing and reviewing various literatures related to research. The data analysis technique used in discussing and analyzing the data is by using descriptive analysis methods and comparative methods. The results showed that the implementation of environmental awareness character education in elementary schools was carried out in three stages, namely: 1) integrated learning planning strengthening environmental care character education. Environmental awareness values ​​are integrated into planning documents such as lesson plans and syllabus. 2) Implementation of integrated learning to strengthen environmental awareness character education. The teacher integrates the values ​​of environmental awareness by utilizing the environment as a learning resource, and arranges classes so that the implementation of environmental awareness characters can run well. 3) Integrated learning assessment of the achievement of environmental awareness character. The character of environmental awareness becomes one of the components of attitude assessment. In addition, the formation of environmental awareness was carried out through positive habits both at home, at school, and in the community. The obstacles in implementing character education in elementary schools are influenced by internal and external factors. Internal factors are students' low understanding of environmental cleanliness. While external factors, namely, inadequate facilities and the indecision of the rules made by the school. The tips taken to support the success of environmental awareness character education in elementary schools, namely: 1) implementation of an environment-based curriculum in schools; 2) participatory based environmental activities; and 3) management of supporting facilities that are environmentally friendly. Thus, it can be concluded that the implementation of environmental awareness character education in schools can run well if there is work between the important components in education, namely teachers, students, parents, and the community.